2014
DOI: 10.1111/odi.12266
|View full text |Cite
|
Sign up to set email alerts
|

Eckols reduce dental pulp inflammation through the ERK1/2 pathway independent of COX‐2 inhibition

Abstract: This study elucidates that EB1 and EB5 have different types of anti-inflammatory property and help in dentin formation. Therefore, these compounds derived from marine algae of E. bicyclis may be used as selective therapeutic strategies for pulpitis and oral diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…The RBL cells were stimulated by antigen-antibody reaction or A23187. According to previously reported phlorotannin concentration ranging 1 to 200 μM in cultured model cell experiments [7,8,10,26,27,28,29], we chose a concentration range from 10 to 200 μM in our experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RBL cells were stimulated by antigen-antibody reaction or A23187. According to previously reported phlorotannin concentration ranging 1 to 200 μM in cultured model cell experiments [7,8,10,26,27,28,29], we chose a concentration range from 10 to 200 μM in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The same two phlorotannins at 100 μM suppressed COX-2 mRNA expression in RBL cells, compared with the other four phlorotannins (Figure 2). It has been reported that the anti-inflammatory effect of 6,6′-bieckol is via the inhibition of COX-2 expression and activity through suppression of NF-κB and ERK 1/2 signaling [28,29]. The suppression effect of 6,6′-bieckol on ear swelling could be attributable to greater suppression of COX-2 mRNA expression than to inhibition of COX-2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that phelligridin D has antioxidant, as well as anti‐inflammatory properties, and is effective against chronic inflammation via downregulation of ICAM‐1 and VCAM‐1. COX‐2 is responsible for prostaglandin synthesis, and related to acute inflammation at the site of inflammation . On the other hand, some recent evidence focusing on the inhibition of COX‐2 is deleterious to cardiovascular patients, and carries the risk of upper gastrointestinal bleeding and perforation, because it increases thrombotic tendencies .…”
Section: Discussionmentioning
confidence: 99%
“…This experiment used 3‐9 passages for PDLCs from each individual. Mineralization experiments for alkaline phosphatase (ALP) and Alizarin red S staining were carried out on cells cultured in 50 μg/mL of ascorbic acid, 10 mmol/L of β‐glycerophosphate and 100 nmol/L of dexamethasone as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Celecoxib (CLX), 4-[5-(4-methylphenyl)-3-trifluromethyl-1H -pyrazol -1-yl} benzenesulfon-amide is a cycloxygenase-2 (COX-2) inhibitor and widely used as analgesic and antiinflammatory (NSAID) in treatment of osteoarthritis, rheumatoid arthritis, familial adenomatous polyposis (FAP), primary dysmenorrhea and dental practice 1,2,3 .…”
Section: Introductionmentioning
confidence: 99%